On the Frontiers of Software Science and Software Engineering - Wang, Yingxu (Frontiers in Computer Science, 2022)
Advances in software engineering, software science, computational intelligence, and intelligent mathematics have led to the establishment of Frontiers in Computer Science—Software (FCSS). FCSS aims to promote transdisciplinary research on software science and engineering (SSE), autonomous systems, and computational intelligence. FCSS covers not only classical empirical software engineering and industrial processes, but also contemporary topics of software science, intelligent programming languages, autonomous code generation, mathematical foundations of software, and programming knowledge bases. FCSS reports empirical studies and emerging topics in software engineering including tools, development platforms, industrial processes, management infrastructures, quality assurance schemes, big data systems, and software migrations across languages and platforms.